Ag@polydopamine-functionalized borate ester-linked chitosan hydrogel integrates monitoring with wound healing for epidermal sensor - Wei Shi; Hui Li; Chengsheng Xu; Gaoyi Wu; Jing Chen; Jinyong Zhang; Lixin Liang; Qingyang Wu; Yongsheng Liang; Guanglin Li; Wei Tang (npj Flexible Electronics)
Abstract Flexible sensors are promising candidates in personalized healthcare, while desired sensors that allow implantation for biomedical applications with optimal sensing and favorable biological properties remain challenges. Here, a multifunctional hydrogel sensor was developed with gallic acid-modified chitosan (CSGA) and 3-carboxyphenylboronic acid-modified chitosan (CSPBA) by encapsulating Ag-decorated polydopamine (Ag@PDA) nanoparticles, namely Ag@PDA-(CSPBA/CSGA). The optimized hydrogel sensor showed desired sensitivity (gauge factor = 2.49), a rapid response/recovery time of 263 ms and good durability. Due to the presence of abundant reactive groups within Ag@PDA-(CSPBA/CSGA), the hydrogel sensor exhibited a comprehensive performance of self-healing, tissue adhesiveness, antioxidative activity, and antibacterial effects against Escherichia coli (92.76%) and Staphylococcus aureus (98.08%). Moreover, the hydrogel sensor could be utilized as a wound dressing, facilitating accelerated wound closure and tissue regeneration. Both subtle activities and large-scale movements could be monitored and distinguished by the hydrogel sensor. This study provides a promising epidermal sensor that offers multifunctionality for health monitoring and wound management.